Role of labor demand in the labor market effects of a pension reform - Johannes Geyer; Peter Haan; Svenja Lorenz; Thomas Zwick; Mona Bruns (Industrial Relations: A Journal of Economy and Society, 2021)
This paper shows that labor demand plays an important role in the labor market reactions to a pension reform in Germany. Employers with a high share of older worker inflow compared with their younger worker inflow, employers in sectors with few investments in research and development, and employers in sectors with a high share of collective bargaining agreements allow their employees to stay employed longer after the reform. These employers offer their older employees partial retirement instead of forcing them into unemployment before early retirement because the older employees incur low substitution costs and high dismissal costs.
Keywords: 330